Public engagement and institutional usage of Facebook in legislative assemblies from the Southeast Region of Brazil - Bernardes, Cristiane Brum (Revista de Sociologia e Política, 2021)
KEYWORDS: Legislatures; Legislative Assemblies; Facebook; Social Media; Public Engagement. ABSTRACT Introduction: In a context of intensification of interactivity, hyperconnectivity and mobility, and expansion of the possibilities of digital contact between legislative institutions and citizens, this study compares how the four legislative assemblies of the Southeast region of Brazil use the institutional profiles created on Facebook. The objective is to understand how the process of public engagement, as conceptualized by Leston-Bandeira (2014), is being carried out by the legislative houses on this platform. Materials and Methods: The recollection of empirical data on the profiles of the legislative assemblies of São Paulo (ALESP), Minas Gerais (ALMG), Rio de Janeiro (ALERJ) and Espírito Santo (ALES) was held between August 2018 and October 2019. The following techniques were applied: 1) in-depth interviews with the managers of digital communication of the houses and 2) comparative analysis of publications and comments on Facebook in the period between August 2018 and January 2019. Profile data were collected through the Netvizz application and later analyzed in Excel. The interviews were conducted between August and December 2018 and in October 2019 in person or via Skype / WhatsApp video. Results: Comparative data reveal that the @assembleiademinas profile made more intense use of Facebook in the period analyzed, despite having fewer followers than the profiles of ALERJ and ALESP. In addition to posting more, ALMG’s profile achieved more interactions with citizens, especially through reactions to some posts made in October and December 2018. Of the four assemblies analyzed, ALES’ profile had the lowest quantitative reach, in number of users who interact, both in reactions and comments. ALMG has the profile that received most reactions per post, while ALESP received more comments per post in the period. Discussion: The most general conclusion is that the four legislative houses analyzed fail to monitor the contributions of internet users and promote a more dialogical interaction with them, focusing on the levels of information, understanding and identification of the process of public engagement. There is, therefore, a difficulty in including aspects of participation and intervention in political decision-making in the dynamics of social media. To a last extent, by not taking advantage of the dialogical potential of networks, legislative assemblies waste opportunities for engagement with the citizen and intensify their distance from society.